Amygdalin from Apricot Kernels Induces Apoptosis and Causes Cell Cycle Arrest in Cancer Cells: An Updated Review - Saleem, Mohammad; Asif, Jawaria; Asif, Muhammad; Saleem, Uzma (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Amygdalin is a cyanogenic glycoside which is described as a naturally occurring anticancer agent. Current review highlights apoptosis-inducing attributes of amygdalin towards different cancers and its potential application as an anti-cancer agent in cancer therapy. Method: Data about amygdalin was retrieved from all major scientific databases i.e., PubMed, ScienceDirect, Google Scholar, Scopus and Medline by using combination of keywords like amygdalin, apoptosis, laetrile, vitamin B- 17, pro-apoptotic proteins, anti-apoptotic proteins, hydrogen cyanide, mechanism of action of amygdalin and amygdalin therapy on humans. However, no specific time frame was followed for collection of data. Results: Data collected from already published articles revealed that apoptosis is a central process activated by amygdalin in cancer cells. It is suggested to stimulate apoptotic process by upregulating expression of Bax (proapoptotic protein) and caspase-3 and downregulating expression of Bcl-2 (anti-apoptotic protein). It also promotes arrest of cell cycle in G0/G1 phase and decrease number of cells entering S and G2/M phases. Thus, it is proposed to enhance deceleration of cell cycle by blocking cell proliferation and growth. Conclusion: The current review epitomizes published information and provides complete interpretations about all known anti-cancer mechanisms of amygdalin, possible role of naturally occurring amygdalin in fight against cancer and mistaken belief about cyanide toxicity causing potential of amygdalin. However, well-planned clinical trials are still needed to be conducted to prove effectiveness of this substance in vivo and to get approval for human use.
Keywords: Bax